MOLECULAR TYPING AND CHARACTERIZATION OF BOVINE PAPILLOMAVIRUS FROM CUTANEOUS WARTS OF CATTLE AND BUFFALO IN TAMIL NADU (INDIA) (Applied Biological Research, 2025)
Bovine papillomavirus (BPV) is a diverse group of oncogenic viruses and the causative agent of bovine papillomatosis, which affects the cattle industry by contributing significant economic losses. The present study was aimed to detect and characterize BPV by molecular methods, namely polymerase chain reaction (PCR) and DNA sequencing. Wart samples (n = 10) were aseptically collected from clinically affected cattle and buffalo. DNA was extracted directly from the wart samples and PCR was performed to detect BPV using BPV-specific L1 gene primers. All wart samples were positive for BPV by PCR, producing an amplicon of 480 bp. Histopathological examination revealed hyperkeratosis, acanthosis, fusion of rete pegs and characteristic rete pegs with koilocytes. DNA sequencing of the conserved L1 gene was carried out for molecular typing of BPV prevailing in the Namakkal district of Tamil Nadu, India. The sequences showed 95.9–100% identity with BPV type 1 of the genus Deltapapillomavirus. Phylogenetic analysis indicated that all sequences clustered with BPV-1. It is concluded that nucleotide sequencing of the L1 fragment is efficient for identification and typing of BPV, and BPV-1 strains were found to be the cause of cutaneous warts in cattle and buffalo.
Keywords: Bovine papillomavirus; molecular typing; nucleotide sequencing; phylogenetic analysis